A critical realist study on the role of food product date labels on household food waste. - Weber, Kirstie Ashleigh (The IIE, 2020)
The Food and Agriculture Organization (FAO) of the United Nations found that globally one-third of food intended for human consumption is lost or wasted (FAO, 2011). Wasted and lost food costs consumers and the supply chain; it wastes crucial resources that are used to grow, process, distribute, and store food (Oxford, 2018). A big portion of the food wasted was found to still be edible and could have gone to those in need, it’s a missed opportunity to feed the millions of food-insecure households (Närvänen, Mesiranta, Mattila, and Heikkinen, 2019). Products have various dates such as expiry dates, best-before dates, use-by dates, and sell-by dates which is confusing and causes uncertainty on whether or not the food is still safe to eat However, we trust the food retailers and manufacturers to guide us in the right direction. As the gatekeepers to the food supply chain, the retail sector is a crucial influence in reducing food waste (Collart and Interis, 2018). Reducing food waste through regulating date labels requires a thorough understanding of consumers’ perceptions of these date labels as well as retailer's and manufacturer's best practices in this regard. This research report used a critical realist lens to assess consumers' perceptions, understanding, and behaviour relating to date labelling and its correlation to household food waste. It also evaluated Pick n Pay as a meaningful brand contributing towards curbing household food waste specifically looking at the retailer's date label practices within their stores and overall waste management behaviour. The research study took on a mixed-method approach to researching consumers and Pick n Pays behaviour concerning the implications of date label interpretations resulting in household food waste. The qualitative and quantitative data was assessed using a content analysis approach. The findings provided a complex reality that highlights the lack of knowledge and sustainability across demographics which needs to be examined to emancipate consumers to ensure food security in South Africa.
Keywords: Food waste and loss; Brand's meaningful purpose; Brand communication; Brand value; Sustainability; Healthy brand; Pick n Pay, South Africa; Retail industry